2020
DOI: 10.1093/cercor/bhaa336
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Rhesus Monkey First Trimester Zika Virus Infection Impacts Cortical Development in the Second and Third Trimesters

Abstract: Zika virus is a teratogen similar to other neurotropic viruses, notably cytomegalovirus and rubella. The goal of these studies was to address the direct impact of Zika virus on fetal development by inoculating early gestation fetal rhesus monkeys using an ultrasound-guided approach (intraperitoneal vs. intraventricular). Growth and development were monitored across gestation, maternal samples collected, and fetal tissues obtained in the second trimester or near term. Although normal growth and anatomical devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Endothelial cells may thus serve as a route for spreading infection widely throughout the body and also an entry point for infectious diseases into the brain. ZIKV has been shown to infect NPCs (Dang et al 2016;Garcez et al 2016;Tang et al 2016), and has also been associated with enlarged cerebral vessels exhibiting abnormal morphology in fetal rhesus monkey and ferret (Hutchinson et al 2019;Tarantal et al 2020), and with impaired development of cerebral vasculature in mouse models (Shao et al 2016;Garcez et al 2018). Given the complex interconnectivity we show here between vessels, NPCs, and microglia in the normally developing cerebrum (Fig.…”
Section: Health Implicationsmentioning
confidence: 58%
See 1 more Smart Citation
“…Endothelial cells may thus serve as a route for spreading infection widely throughout the body and also an entry point for infectious diseases into the brain. ZIKV has been shown to infect NPCs (Dang et al 2016;Garcez et al 2016;Tang et al 2016), and has also been associated with enlarged cerebral vessels exhibiting abnormal morphology in fetal rhesus monkey and ferret (Hutchinson et al 2019;Tarantal et al 2020), and with impaired development of cerebral vasculature in mouse models (Shao et al 2016;Garcez et al 2018). Given the complex interconnectivity we show here between vessels, NPCs, and microglia in the normally developing cerebrum (Fig.…”
Section: Health Implicationsmentioning
confidence: 58%
“…9), endothelial cells that become functionally impaired through infection may further compromise nervous system development. Indeed, we have found that Zika administration to fetal rhesus monkeys produced abnormalities in microglial cell and Tbr2 + cell distribution, blood vessel morphology, and is correlated with thinner cortical gray matter (Tarantal et al 2020). Other conditions including schizophrenia, hydrocephaly, and children born of pre-eclamptic pregnancies have also been correlated with vascular abnormalities (Webster et al 2001;Lara et al 2018;Fehnel et al 2019).…”
Section: Health Implicationsmentioning
confidence: 84%
“…Because vRNA was not detected in any fetal tissues, our results may suggest that vertical transmission did not occur between dam 049-101 and the developing fetus. Alternatively, the results may suggest immunologic elimination of virus at later gestational ages as previously suggested by a study using direct fetal ZIKV inoculation (43). Our decision to challenge the animals in this study early in pregnancy (~30 days gestation) was based on findings in humans suggesting that during the first trimester, ZIKV infection is associated with a higher risk of adverse fetal and pregnancy outcomes (27,50-53)( 43) (27,(50)(51)(52)(53).…”
Section: Introductionmentioning
confidence: 86%
“…Hysterotomy and tissue collection Dams 049-102 and 049-103 were scheduled for hysterotomies in the late first trimester (nonviable embryos detected days prior to hysterotomy). The hysterotomy for dam 049-101 was performed at approximately 155 days gestational age according to the original study design (Figure 1) and following established protocols (43). The gestational sac was removed for fetal tissue assessments, with a modified collection protocol for nonviable specimens (see below).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation